Inequalities in Access to Health Services: The Case of Greece - Douki, Stamatina; Spyridakis, Emmanouil (HAPSc Policy Briefs Series, 2024)
Health inequalities, which can be categorized into inequalities in health and in the provision of care, arise from the differentiation of citizens based on their socioeconomic characteristics. Greece is classified as a country with a high degree of health inequalities. This research study aims to investigate health inequalities in general, with a particular focus on the case of Greece. The methodology involved a search for contemporary international literature collected from electronic databases such as PubMed and Google Scholar, excluding studies in languages other than English or Greek. A thorough review of the literature highlighted the necessity of universal health care that prioritizes the individual and their health needs.